2010
DOI: 10.1097/yct.0b013e3181a95d8c
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of QT Interval Induced by Electroconvulsive Therapy is Attenuated by Landiolol

Abstract: The prolongation of QT interval caused by SUX and ECT was partially attenuated by landiolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…With respect to the QTc interval, it has been pointed out that mECT can provoke prolongation of QTc intervals [17,18]. In our patient, the QTc interval spread to 0.46 s following the convulsions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…With respect to the QTc interval, it has been pointed out that mECT can provoke prolongation of QTc intervals [17,18]. In our patient, the QTc interval spread to 0.46 s following the convulsions.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is clear that, under the condition of uncontrolled hemodynamics, considerable sympathotonic increases in BP and HR following the electric stimuli augmented the cardiac oxygen demand, myocardial contractility, and serum catecholamine level, resulting in relative myocardial ischemia [20]. Therefore, the use of calcium channel and/or beta blockers before applying electric stimuli should be considered in order to attenuate hemodynamic hyperactivity [8,15,17]. We used nicardipine, a calcium channel blocker, against persisting hypertension even after the restoration of normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with d-tubocurarine, 76 or selective b-1 blockers (practolol, 77 metoprolol, 77 landiolol, 112 possibly esmolol), 79 99 attenuates the QT and QTc lengthening induced by succinylcholine. A similar effect was also demonstrated for alfentanil 25-75 mg kg 21 , 98 -100 but not for smaller doses (10 mg kg 21 ), 100 suggesting a dose-related effectiveness.…”
Section: Neuromuscular Blocking and Reversal Agentsmentioning
confidence: 99%
“…Landiolol, an ultrashort acting β-1 blocker, is 9 times more potent in β-1 blocking activity and 8 times more cardioselective than esmolol. 3,5,8 Previous studies 5,8 have demonstrated the efficacy of landiolol for the stabilization of systemic hemodynamics; however, the appropriate dose for the stabilization of all parameters, systemic blood pressure, cardiac output, and cerebral blood flow velocity has yet to be reported. Our study findings suggest that 0.25 mg/kg of landiolol may be an adequate dose for preventing an increase in systemic hemodynamics, including cardiac output, despite having no effect on prevention of the increase in middle cerebral artery (MCA) flow velocity.…”
Section: Discussionmentioning
confidence: 97%